Pengaruh Kepemimpinan Demokratis dan Motivasi Kerja Terhadap Kinerja Dosen Pada STAI Ibnu Sina Batam Kepulauan Riau - Rosnawati Rosnawati; Lias Hasibuan; Kasful Anwar Us (AkMen JURNAL ILMIAH, 2021)
This study aims to determine and analyze: The Effect of Democratic Leadership and Work Motivation on Lecturer Performance at STAI Ibnu Sina Batam, Riau Islands. This research approach uses survey research. The time of the research was carried out starting in March 2021. The research population was 31 lecturers who taught at STAI Ibnu Sina Batam, Riau Islands. The sample selection in this study was carried out using the census method where the population acted as a sample. The results show that: 1) There is a positive and significant influence of democratic leadership individually (partial) on the performance of lecturers at STAI Ibnu Sina Batam, Riau Islands, with tcount = 3.936 > ttable = 1.99. 2) There is no positive and significant effect of work motivation individually (partial) on the performance of lecturers at STAI Ibnu Sina Batam, Riau Islands, with tcount = 0.195 < ttable = 1.99. 3) There is a simultaneous (simultaneous) influence of democratic leadership and work motivation on the performance of lecturers at STAI Ibnu Sina Batam, Riau Islands, where Fcount = 12.841 > Ftable = 2.73. Based on the results of the study, the coefficient of determination (R2) was 0.478 or (47.8%). This shows that 47.8% of lecturers' performance is influenced by democratic leadership and work motivation. While 52.2% is influenced by other variables that are not included in this research model.